A hierarchical meta‐analysis for settings involving multiple outcomes across multiple cohorts. Issue 1 (24th June 2022) - Akkaya Hocagil, Tugba; Ryan, Louise M; Cook, Richard J.; Jacobson, Sandra W.; Richardson, Gale A.; Day, Nancy L.; Coles, Claire D.; Carmichael Olson, Heather; Jacobson, Joseph L.
Abstract : Evidence from animal models and epidemiological studies has linked prenatal alcohol exposure (PAE) to a broad range of long‐term cognitive and behavioural deficits. However, there is a paucity of evidence regarding the nature and levels of PAE associated with increased risk of clinically significant cognitive deficits. To derive robust and efficient estimates of the effects of PAE on cognitive function, we have developed a hierarchical meta‐analysis approach to synthesize information regarding the effects of PAE on cognition, integrating data on multiple outcomes from six U.S. longitudinal cohort studies. A key assumption of standard methods of meta‐analysis, effect sizes are independent, is violated when multiple intercorrelated outcomes are synthesized across studies. Our approach involves estimating the dose–response coefficients for each outcome and then pooling these correlated dose–response coefficients to obtain an estimated "global" effect of exposure on cognition. In the first stage, we use individual participant data to derive estimates of the effects of PAE by fitting regression models that adjust for potential confounding variables using propensity scores. The correlation matrix characterizing the dependence between the outcome‐specific dose–response coefficients estimated within each cohort is then run, while accommodating incomplete information on some outcome. We also compare inferences based on the proposed approach to inferences based on a full multivariate analysis.